GLOBALISATION AND SUB-STATE NATIONALISM: A REVIEW AND ANALYSIS OF THE INTERRELATION BETWEEN GLOBALISATION AND THE RISE OF MINORITY NATIONALISM - Anwar Anaid (European Scientific Journal, ESJ, 2014)
This article evaluates and analyses the literature on the relationship between minority nationalism and the process of globalisation and identifies the key trends in nature and direction of the modern sub-state nationalism. The finding suggests that the creation of opportunities by globalisation for minority nations is dependant on the level of the economic development and economic integration of sub-state entities and their host nation-states. The overall picture that emerges from analysis of the economic data suggests that it is mainly the minorities in developed countries that are reported to benefit from economic globalisation for the promotion of their nationalist agenda through peaceful means. The paper consists of three parts. In part I, some cases of sub-state nationalisms in developed countries are reviewed. In part II the result of studies on minority nationalism in relatively developed and developing countries are examined and in part III, a summary and analysis of the key findings is provided. Through an examination of the GDP figures, the relation between the level of economic development and the reported rise of sub-state nationalism is evaluated. A similar process is repeated for evaluating the relationship between the level of economic integration and the reported opportunities for sub-state nationalists and relevant trade data is used for this purpose. Other factors such as the impact of suprastate entities, the role of new global economic order and sub-state’s instrumental approach to globalisation are also considered.